Mental health impacts of African swine fever outbreaks on veterinarians in the Philippines - Bakke, Hannah J.; Perez, Alejandro D.; Miclat-Sonaco, Ruth; Perez, Andres M.; Schambow, Rachel A. (Frontiers in Veterinary Science, 2025)
Emergence of African swine fever (ASF) in the Philippines in 2019 caused substantial impacts on animal health and its pig industry. To control ASF, strict policies were applied including zoning and depopulation of infected herds. While ASF’s severe impacts on pigs are well recognized, its potential impacts to public health are often overlooked. ASF is not a food safety concern and does not infect humans, but it has the potential to affect mental, emotional, and social well-being during emergency response. Veterinarians may be particularly at risk due to their role in depopulation of pigs and other distressing tasks. The objective here was to assess the effects of the ASF outbreaks on Filipino veterinarians’ mental and social well-being. A questionnaire was created and anonymously administered to 13 Filipino veterinarians attending a training workshop in December 2023. All participants had experience responding to the ASF outbreaks. Then, the summary responses were discussed with the entire group, allowing for clarification and verification. Two-by-two contingency tables and Fisher’s exact test were used to explore associations between responses. The top five negative signs reported by >50% participants were “reduced energy,” “reduced sleep,” “new feelings of hopelessness or sadness,” “new feelings of anger or frustration,” and “reduced enjoyment of life.” Some veterinarians also reported negative social interactions such as antagonism and blame toward public veterinarians. These results highlight the often-overlooked impacts of ASF on mental and social well-being and indicate the need for mental health support for veterinarians as part of comprehensive ASF mitigation efforts.